Analisis Efektivitas Komunikasi Tulis Baca Konfirmasi dalam Sasaran Keselamatan Pasien di Ruang Rawat Inap Rumah Sakit X Jepara - Sinta Nurani; Sudiro Sudiro (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2019)
Communication is one of the root causes of mismanagement of medical actions, lack of division of labor and coordination between professions as one of the cultural barriers to safety enforcement in hospitals. Hospitals must have a list of permitted or prohibited abbreviations which can often lead to fatal communication errors. Doctors in private hospitals in regions such as the